All together now : creating middle-class schools through public school choice - Kahlenberg, Richard D. (Washington, D.C. : Brookings Institution Press, 2001)
Annotation "In All Together Now, Richard D. Kahlenberg offers a provocative idea for improving public education: give every American child the right to attend a school in which the majority of students come from middle-class homes." "Kahlenberg combines Mann's nineteenth-century concept of the common school - which calls for educating disadvantaged and advantaged children under one roof - with the current enthusiasm for choice among public schools. This new concept, common school choice, would allow families to choose the best school for their children from a number of middle-class public institutions."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved
American schools today: falling short of our goals -- The case for economic school desegregation -- The significance of the socioeconomic makeup of schools -- The difficulty with alternatives to socioeconomic integration -- How socioeconomic integration can be achieved in practice -- Political and legal strategies -- Rebutting the case against socioeconomic integration -- Practical experience with socioeconomic integration.
"A Century Foundation book."
Includes bibliographical references (pages 258-366) and index.
Print version record.
JSTOR
Keywords: Educational equalization -- United States; Education -- Economic aspects -- United States; Public schools -- United States; Démocratisation de l'enseignement -- États-Unis.; Éducation -- Aspect économique -- États-Unis.; Écoles publiques -- États-Unis.; EDUCATION -- Educational Policy & Reform -- General; EDUCATION -- Administration -- General; Education -- Economic aspects; Educational equalization; Public schools; United States